OPRM1 A118G Polymorphisms and Its Role in Opioid Addiction: Implication on Severity and Treatment Approaches - Taqi MM; Faisal M; Zaman H (Dove Medical Press, 2019)
Malik Mumtaz Taqi,1 Muhammad Faisal,2,3 Hadar Zaman4 1Division of Mental Health and Addiction, University of Oslo, Oslo, Norway; 2Faculty of Health Studies, University of Bradford, Bradford, UK; 3Bradford Institute for Health Research, Bradford Teaching Hospitals NHS Foundation Trust, Bradford, UK; 4School of Pharmacy and Medical Sciences, Faculty of Life Sciences, University of Bradford, Bradford, UKCorrespondence: Muhammad FaisalFaculty of Health Studies, University of Bradford, Richmond Road, Bradford BD7 1DP, UKEmail M.Faisal1@bradford.ac.ukAbstract: The epidemic of opioid addiction is shaping up as the most serious clinical issues of current times. Opioids have the greatest propensity to develop addiction after first exposure. Molecular, genetic variations, epigenetic alterations, and environmental factors are also implicated in the development of opioid addiction. Genetic and epigenetic variations in candidate genes have been identified for their associations with opioid addiction. OPRM1 nonsynonymous single nucleotide polymorphism rs1799971 (A118G) is the most prominent candidate due to its significant association with onset and treatment of opioid addiction. Marked inter-individual variability in response to available maintenance pharmacotherapies is the common feature observed in individuals with opioid addiction. Several therapies are only effective among subgroups of opioid individuals which indicate that ethnic, environmental factors and genetic polymorphism including rs1799971 may be responsible for the response to treatment. Pharmacogenetics has the potential to enhance our understanding around the underlying genetic, epigenetic and molecular mechanisms responsible for the heterogeneous response of maintenance pharmacotherapies in opioid addiction. A more detailed understanding of molecular, epigenetic and genetic variants especially the implication of OPRM1 A118G polymorphism in an individual may serve as the way forward to address the opioid epidemic. Personalized medicine, which involves developing targeted pharmacotherapies in accordance with individual genetic and epigenetic makeup, are required to develop safe and effective treatments for opioid addiction.Keywords: opioid addiction, personalized medicine, pharmacotherapies, epigenetic and genetic variants